New therapeutic modalities for rare diseases - Fatih S. Ezgu (Elsevier, 2024)
Genetic Diseases affect about 2 % to 3 % of all live births. It has been reported that genetic disorders can account for up to 22 % of infant deaths. Despite this significant effort to create new therapies, treatment is available only for about 5 % of these diseases due to undiscovered etiology or rapid progression to the point of no return. Efforts for new and effective etiology-targeted treatment methods for rare genetic disorders have significantly increased in recent years. Gene-targeted novel treatments such as gene replacement therapy and gene editing, mainly gene-targeted, have significant potential to be the primary treatment modalities in the future.